Angiotensin-converting enzyme 2 is subject to post-transcriptional regulation by miR-421 - Lambert, Daniel W; Lambert, Louise A; Clarke, Nicola E; Hooper, Nigel M; Porter, Karen E; Turner, Anthony J (Clinical science (1979), 2014)
ACE2 (angiotensin converting enzyme 2) plays a critical role in the local tissue RAS (renin-angiotensin system) by hydrolysing the potent hypertensive and mitogenic peptide AngII (angiotensin II). Changes in the levels of ACE2 have been observed in a number of pathologies, including cardiovascular disease, but little is known of the mechanisms regulating its expression. In the present study, therefore, the potential role of miRNAs in the regulation of ACE2 expression in primary human cardiac myofibroblasts was examined. Putative miRNA-binding sites were identified in the 3'-UTR of the ACE2 transcript using online prediction algorithms. Two of these, miR-200b and miR-421, were selected for further analysis. A reporter system using the 3'-UTR of ACE2 fused to the coding region of firefly luciferase was used to determine the functionality of the identified binding sites in vitro. This identified miR-421, but not miR-200b, as a potential regulator of ACE2. The ability of miR-421, an miRNA implicated in the development of thrombosis, to down-regulate ACE2 expression was subsequently confirmed by Western blot analysis of both primary cardiac myofibroblasts and transformed cells transfected with a synthetic miR-421 precursor. Real-time PCR analysis of miR-421 revealed widespread expression in human tissues. miR-421 levels in cardiac myofibroblasts showed significant inter-patient variability, in keeping with the variability of ACE2 expression we have observed previously. In conclusion, the present study is the first to demonstrate that ACE2 may be subject to post-transcriptional regulation and reveals a novel potential therapeutic target, miR-421, which could be exploited to modulate ACE2 expression in disease.